Walnut consumption increases activation of the insula to highly desirable food cues: A randomized, double-blind, placebo-controlled, cross-over fMRI study - Farr, Olivia M. (Diabetes Obes Metab, 2017)
AIMS: The use of walnuts is recommended for obesity and type 2 diabetes, although the mechanisms through which walnuts may improve appetite and/or glycemic control remain largely unknown. MATERIALS AND METHODS: To determine whether short-term walnut consumption could alter the neural control of appetite using functional magnetic resonance imaging, we performed a randomized, placebo-controlled, double-blind, cross-over trial of 10 patients who received, while living in the controlled environment of a clinical research center, either walnuts or placebo (using a validated smoothie delivery system) for 5 days each, separated by a wash-out period of one month. RESULTS: Walnut consumption decreased feelings of hunger and appetite assessed using visual analog scales and increased the activation of the right insula to highly desirable food cues. CONCLUSIONS: These findings suggest that walnut consumption may increase salience and cognitive control processing of highly desirable food cues, leading to the beneficial metabolic effects observed.